ANALISIS HUMAN RELIABILITY ASSESSMENT (HRA) DENGAN METODE HUMAN ERROR ASSESSMENT AND REDUCTION TECHNIQUE (HEART) TERHADAP TRAIN WATCHER PADA PROYEK PEMBANGUNAN FASILITAS PERKERETAAPIAN OLEH PT X TAHUN 2021 - Ambrita Estuningtyas (2022)
Work accidents on railways and roads are included in the scope of work accidents. Central Statistics Data Agency stated in both 2019 and 2020 there was an increase in work accident cases of 6.59%. Therefore, to support the safety aspects of these projects, there is no need for a Train Watcher. The role of Train Watchers in upholding work safety is important. If Train Watcher makes the slightest possible error, it can cause an accident. This study aims to help identify and recognize Train Watcher's failures/negligence in carrying out their work using Human Error Assessment and Reduction Technique (HEART) method. This type of research uses descriptive and qualitative study designs. From discussions with main informant (HSE) and Train Watcher are role or task of the Train Watcher as well as the bored pile work holds the highest Human Error Potential (HEP) value, with the work stages of mobilizing work tools with a score of 43.08, who they did not ensure the position of heavy equipment that did not exceed the active track area. Therefore, it is recommended to informants to take sufficient rest and for Company X to advise Train Watcher personnel and make shift policies for Train Watchers.